2013
DOI: 10.1007/s10862-013-9338-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Age of Onset to the Psychopathology of Social Phobia

Abstract: The present study aimed to examine the relevance of age of onset to the psychopathology of social phobia using a large clinical sample of 210 patients with social phobia. The two most common periods of onset were during adolescence (ages 14–17) and early childhood (prior to age 10). Structural regression modeling was used to test predictions that early onset social phobia would be associated with greater severity of the disorder, stronger current symptoms of depression and anxiety, greater functional impairmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…The other study did not find predictive effects for any co-morbidity (Kessler et al 2005). Another possible reason for the lack of association between social phobia and persistence in childhood ADHD is the fact that a significant fraction of cases of social phobia starts during or after adolescence (Rosellini et al 2013). Previous studies have suggested that both oppositional defiant disorder and social phobia may be related with a worse response to treatment as well as with some difficulty to engage in clinical interventions (Souery et al 2007;Stringaris & Goodman, 2009;).…”
Section: Discussionmentioning
confidence: 84%
“…The other study did not find predictive effects for any co-morbidity (Kessler et al 2005). Another possible reason for the lack of association between social phobia and persistence in childhood ADHD is the fact that a significant fraction of cases of social phobia starts during or after adolescence (Rosellini et al 2013). Previous studies have suggested that both oppositional defiant disorder and social phobia may be related with a worse response to treatment as well as with some difficulty to engage in clinical interventions (Souery et al 2007;Stringaris & Goodman, 2009;).…”
Section: Discussionmentioning
confidence: 84%
“…Based on these studies, early maladaptive schema as a deeper cognitive variable affects social phobia through behavioral-cognitive variables (perception of others' negative assessment, negative selfassessment and behavioral inhibition). The main feature of social phobia is a distinguished and stable fear of social situations in which one might be confused and embarrassed because people with social phobia believe that their behaviors would socially have catastrophic consequences (22). In the past few decades, many theoretical models were represented to explain the mechanism underlying this distinguished fear of social situations in particular and social phobia in general, some of which emphasized the cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Among anxiety disorders, SAD has one of the earliest onset and, without intervention, tends to follow a chronic course (Brown et al 2001 ;Burstein et al 2011 ;Juster and Heimberg 1995 ;Reich et al 1994 ;Rosellini et al 2013 ;Stein and Stein 2008 ). In fact, the median age of onset of SAD appears to be more accurately described as bimodal; in one large sample of individuals presenting for treatment, 21 % reported an age of onset before the age of 10, and 47.6 % reported an age of onset during adolescence/early adulthood (14-22) (Rosellini et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the median age of onset of SAD appears to be more accurately described as bimodal; in one large sample of individuals presenting for treatment, 21 % reported an age of onset before the age of 10, and 47.6 % reported an age of onset during adolescence/early adulthood (14-22) (Rosellini et al 2013 ). Age of onset in the middle childhood years (10-14) or adult years (over 23) 1 is relatively rare (Rosellini et al 2013 ;Wittchen and Fehm 2003 2 ). For more details, please see Chap.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation